Pelatihan Pemastian Mutu Bahan Baku Tanaman Obat dan Pembuatan Produk Jamu Sebagai Upaya Pengembangan Program Desa Rempah di Desa Gombengsari - Nurmalasari, Dewi Riskha; Nuraini, Fathiyah Rizki; Handojo, Kukuh Judy; Maulani, Dyan; Dwijayanti, Anies Rahman (Fakultas Kedokteran Gigi, Universitas Jember, 2025)
Medicinal plants in Indonesia consist of various species that have similar morphological structures that are difficult to distinguish from one another. In terms of ensuring the safety of using a medicinal plant, quality assurance and quality control are needed. Good quality medicinal plants can be obtained by standardizing medicinal plant raw materials, standardizing production processes, traditional medicinal products, distribution methods, and effective dosages. Gombengsari is part of Banyuwangi Regency. The main commodities in the area are coffee and other plantation commodities such as coconut, cloves, and medicinal plants. The purpose of the community service program is to provide education and training to our Community Service Partners, namely POKMAS Sumberwaru Maju, on how to ensure the quality of medicinal plant raw materials, as well as an effort to develop the Spice Village Program (Toga Village) in Gombengsari. The stages of the activity include: pretest, education or counseling, training in making herbal drinks, posttests, and assisting in the production of herbal products. The results of this counseling and training activity, as well as the mentoring that we have done, have a positive and beneficial impact on the group. This can be seen from the group actively practicing the knowledge that we have taught to the group team. This community service activity is planned to continue with a different theme, but still on interrelated material in Gombengsari Village.Keywords: Medicinal plants, traditional medicinal products, quality assurance